Financial Literacy Assistance and Utilization of Management Information Systems for Stock Investment Decision Making in the Indonesian Capital Market - Wicaksono, M. Fadli; Imsar, Imsar; Nurbaiti, Nurbaiti (Amalee: Indonesian Journal of Community Research and Engagement, 2024)
The Indonesian capital market has experienced significant growth supported by advances in information technology, particularly the implementation of Management Information Systems (MIS) in investment decision-making. This study aims to analyze the role of MIS in enhancing the efficiency and accuracy of stock investment decisions in the Indonesian capital market. A qualitative research method using in-depth interviews with individual investors was employed to explore their experiences and perceptions in using MIS. The results indicate that MIS facilitates real-time data access, improves the quality of fundamental and technical analysis, and assists in investment risk management. However, challenges such as data quality, interface complexity, and low financial literacy hinder the optimal use of MIS. This study recommends improving data quality, developing more user-friendly features, and providing continuous financial literacy education programs to maximize MIS utilization. The findings are expected to serve as a reference for MIS developers and capital market regulators in strengthening an inclusive and sustainable investment ecosystem.